Mechanism of direct C-H arylation of pyridine via a transient activator strategy : a combined computational and experimental study - Jia, Feiyun (2020)
Recently, we realized the highly selective one-pot synthesis of 2,6-diarylpyridines by using a Pd-catalyzed direct C-H arylation approach via a transient activator strategy. Although methylation reagent as a transient activator and Cu(I) salt or oxide were found to be prerequisites, details regarding the mechanism remained unclear. In this paper, DFT calculations combined with experimental investigations were carried out to elucidate the principle features of this transformation. The results reveal (1) the origin of the exquisite diarylating selectivity of the pyridine under the transient strategy; (2) the possible demethylating reagent as the counteranion of the pyridinium salt; (3) the reason why Cu2O is a better Cu(I) resource than others.